2014
DOI: 10.1007/s10120-014-0408-5
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing gastric cancer screening by gastrointestinal X-ray with serology for Helicobacter pylori and pepsinogens followed by gastrointestinal endoscopy

Abstract: Background Based on the results of several case-control and cohort studies gastrointestinal X-ray (GI X-ray) has been recommended for use in the nationwide screening program for gastric cancer.. Although this was the only effective screening program when almost all of the Japanese population were Helicobacter pylori (H. pylori) positive, there has been concern whether an alternative effective screening system should be established for the future H. pylori-negative generation. We therefore conducted the first r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It cannot be completely denied that the participants in the ABC method received harmful effects associated with low quality. To make the ABC method more practical for communities, a large epidemiological study is desirable [26] .…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be completely denied that the participants in the ABC method received harmful effects associated with low quality. To make the ABC method more practical for communities, a large epidemiological study is desirable [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to determine the current status of H. pylori infection in children to predict the future incidence of H. pylori-related diseases, including gastric cancer. which could be incorporated into a prevention strategy [9,10]. However, the Electronic supplementary material The online version of this article (doi:10.1007/s10120-017-0688-7) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…PG I ≤70 g/L and PG I/II ratio ≤3.0 are used as the diagnostic thresholds for atrophic gastritis. In Europe and Japan, this threshold is widely used for the screening of high‐risk groups for gastric cancer . In the high‐risk areas of gastric cancer in China, the standard of PG I ≤70 g/L and PG I/II ratio ≤7.0 is used for screening, but there is currently a lack of large follow‐up data for verification.…”
Section: Outcomes Of Chronic Gastritis and The Prevention Of Gastric mentioning
confidence: 99%
“…In Europe and Japan, this threshold is widely used for the screening of high-risk groups for gastric cancer. 159 In the highrisk areas of gastric cancer in China, the standard of PG I ≤70 g/L and PG I/II ratio ≤7.0 is used for screening, 160 but there is currently a lack of large follow-up data for verification. Several studies [161][162][163] have demonstrated that serum PG test contributes to risk stratification in high-risk groups for gastric cancer.…”
Section: Statement 45mentioning
confidence: 99%